THE EFFECT OF PLANNING, BUDGETING AND PARTICIPATION OF BUDGETING ON THE PERFORMANCE OF REGIONAL WORK UNITS IN PIDIE JAYA DISTRICT - Zubir, Muhammad; Naz'aina, Naz'aina; Ratna, Ratna (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2022)
This study aims to determine the effect of planning, budgeting and budgeting participation on the performance of regional work units in Pidie Jaya Regency. This study uses a quantitative approach, the method used is a survey method. Data collection in this study is a systematic and standard procedure to obtain the data needed in the study obtained by distributing questionnaires to 104 selected respondents. The results showed that planning had a positive and insignificant effect on the performance of regional apparatus in Pidie Jaya Regency, budgeting had a positive and significant effect on the performance of regional apparatus in Pidie Jaya Regency and Participation in Budgeting had a positive and insignificant effect on the performance of regional apparatus in Pidie Jaya Regency.